Morphological and metric features of nematodes Haemonchus contortus (Rudolphi 1803) Cobb 1898 isolated from sheep (Ovis aries Linnaeus, 1758) - Мельничук, В. В. (Scientific Progress & Innovations, 2018)
The results of the determination of the features of the imaginal forms structure of nematodes of the species Haemonchus contortus (Rudolphi 1803) Cobb 1898, which parasitize in domestic ovaries (Ovis aries), in the climatic conditions of the central and South-Eastern regions of Ukraine are presented, taking into account their morphometric indices. It has been established that the specific features of the H. contortus males are the features of the morphological structure of the caudal bursa, spicules, shank, sexual cone, and their metric indices. The females of H. contortus have a specific for this species variability in the structure, shape, size, and number of cuticular valves in the vulva.